Petrography of the Baghanwala Formation, Khewra Gorge, Khewra, Jehlum District; Punjab; Pakistan - Khan, Muhammad Attaullah; Khan, Muhammad Javed (Journal of Himalayan Earth Sciences, 1979)
This paper presents a petrographic study of the Baghanwala Formation (Late Early Cambrian-Early Middle Cambrian), exposed in the Kkewra Gorge, Salt Range, Pakistan. The Baghanwala Formation is dominantly composed of shales. Inter-beddings of flaggy sandstone occur at several stratigraphic levels. Thin bands of dolomite/limestone are also interlaminated ii.1 the lower part. Iron oxide coating of the quartz grains which forms the bulk of the detrital fraction of the interlaminated sandstones is a most conspicuous feature. Carbonates (calcite/dolomite) are the other major minerals which form bulk of the matrix. Other detrital minerals present are micas (biotite and muscovite), chlorite, plagioclase, microcline, glauconite, and ores. Carbonates, clay, and iron oxide are the cementing materials.